La hora del cuento en español - Rojas-Primus, Constanza; Rodríguez, Sofía (Open textbook library., 2023)
La hora del cuento en español is a collection of children’s stories in Spanish authored by Kwantlen Polytechnic University (KPU) students and edited by KPU Faculty Constanza Rojas-Primus and KPU alumna Sofía Rodríguez. The first part of this collection is a selection of stories written by KPU Spanish 1100 students between Fall 2017 and Spring 2019 as a result of a collaboration between KPU Spanish and Guildford Public Library Language Literacy Program “Storytime in Spanish”. The second part of this collection is a selection of stories written by KPU Spanish 1101 students between Fall 2020 and Spring 2022 as a result of an interuniversity collaboration in support of UNESCO´s Sustainable Development Goals Agenda 2030. All stories are narrated by Constanza Rojas-Primus and have been translated into English by Sofía Rodríguez. The illustrations in the cover and first part of this collection are artwork of KPU Fine Arts student Cheyenne Pokeda.